MARCUS LUTTRELL'S INTERPRETATION OF THE EVENTS OF OPERATION "RED WINGS": A HISTORICAL AND CRITICAL ANALYSIS - Pavliuk, Artem (Young Scholars Grinchenko – Seton International Journal, 2026)
This article examines the interpretation of the events of Operation “Red Wing” by U.S. Navy SEAL Marcus Luttrell and compares his account with alternative sources, including journalistic investigations, veteran testimonies, and historical analyses. The study argues that many elements of Luttrell’s memoir, Lone Survivor, were exaggerated or distorted, particularly the number of Taliban fighters, the conduct of the battle, and the operational circumstances. The article also analyzes the planning failures and command decisions that contributed to the tragedy and subsequent mythologization of the operation. Special attention is devoted to the impact of these distortions on historical memory, military ethics, and the perception of the fallen servicemen.